Glottophobia and linguistic discrimination: A field study of dialect stigmatization mechanisms and exclusionary practices in Tunisian society - Haj Sassi, Mohamed Fadhel (Social Empowerment Journal, 2025)
The study of dialects is not merely a scientific whim that we can be wary of or reject under the guise of intellectualism, but rather an urgent scientific and cognitive necessity in an era dominated by tendencies toward hegemony and influence in all its forms. This type of study can provide an objective and accurate sociocultural reading of society, as it focuses on the essence of local cultural identity and what that may represent in terms of self-esteem and pride on the one hand, and, on the other hand, the stigmatization and discrimination against others on that basis, despite the fact that the differentiation between dialects is not in line with the modern linguistic view that recognizes the dynamism and social nature of language. We highlighted this in the first part of the research, before moving on to present a historical overview of the phenomenon of linguistic stigmatization through the term “barbarism,” which is considered its oldest manifestation. We then highlighted how language and dialect can transform from stigmatizing conflict to distinctive glottophobia. In the field, we showed that dialect stigmatization in Tunisia is a manifestation of regionalism and its other, more dangerous and painful side, as stigmatization can turn into discriminatory practices that threaten social cohesion and unity.